2014
DOI: 10.1073/pnas.1419272111
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional program of Kpna2/Importin-α2 regulates cellular differentiation-coupled circadian clock development in mammalian cells

Abstract: The circadian clock in mammalian cells is cell-autonomously generated during the cellular differentiation process, but the underlying mechanisms are not understood. Here we show that perturbation of the transcriptional program by constitutive expression of transcription factor c-Myc and DNA methyltransferase 1 (Dnmt1) ablation disrupts the differentiation-coupled emergence of the clock from mouse ESCs. Using these model ESCs, 484 genes are identified by global gene expression analysis as factors correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 38 publications
6
66
0
Order By: Relevance
“…; Umemura et al . , ). We introduced a large deletion of protein coding sequences spanning across exons 3 and 4 in PER2 Luc knock‐in ESCs with the CRISPR/Cas9 system using two sgRNA‐targeting sites and obtained several mutant cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…; Umemura et al . , ). We introduced a large deletion of protein coding sequences spanning across exons 3 and 4 in PER2 Luc knock‐in ESCs with the CRISPR/Cas9 system using two sgRNA‐targeting sites and obtained several mutant cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the course of our studies, a recent report documented a role for MYC in disrupting the emergence of the circadian clock during differentiation of embryonic stem cells (Umemura et al, 2014). However, in these normal cells, MYC disruption of the circadian clock was dominated by a block in PER nuclear import rather than a direct effect on circadian E-boxes as we demonstrated in cancer cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…It has yet to be demonstrated that testis from other mammals, including humans, do not have circadian rhythms; however, based on the data presented here, we speculate that high levels of PASD1 in human testis could lead to suppression of circadian rhythms in the germline (Cooper et al, 2006). Connections between the lack of circadian cycling in undifferentiated embryonic stem cells and the germline are just coming to light (Paulose et al, 2012; Umemura et al, 2014; Yagita et al, 2010), making PASD1 an interesting link that could be explored further.…”
Section: Discussionmentioning
confidence: 99%